ANTITUBERCULOSIS DRUG DOSAGE FORMS: RANGE, KEY BENEFITS AND PROSPECTS OF TECHNOLOGICAL IMPROVEMENT - M. E. Kim; K. B. Murzagulova; E. F. Stepanova (Фармация и фармакология (Пятигорск), 2016)
Interest to research in the development of new formulations of antituberculosis drugs due to the high incidence of tuberculosis in the Republic of Kazakhstan and the Russian Federation nowadays, including with acquired drug resistance. The reason for the development of acquired drug resistance is to interrupt the treatment of patients is the high toxicity of antituberculosis drugs. The improving the efficiency of antituberculosis therapy remains one of the most pressing.The aim this study was to review the dosage forms of antituberculosis drugs currently used and the ways to improve them.Methods. The study was conducted on the basis of scientific analysis (eLibrary database, PubMed, Cyberleninca), patent (kzpatents), reference (Klifar, Drugs register) and technical literature.Results. It was revealed that the antituberculosis drugs are available in the form of tablets, capsules, granules for oral use and injection solutions. The advantages and disadvantages of oral dosage forms of antituberculosis drugs: tablets, capsules, granules, syrups, suspensions are described. The importance of the development and implementation in practice of pediatric formulations of antituberculosis drugs is mentioned. The state of current research inhaled formulations for the treatment of tuberculosis is described. The prospects of directional inhalation exposure by immobilization of antituberculosis drugs in liposomes, niosomes, nanocapsules, micelles, micro- and nanoparticles are mentioned. The prospect of the rectal formulations use is described. The increase in interest in the molecular encapsulation of medicinal substances with cyclodextrins in connection with the possibility of increasing the bioavailability of active ingredients, reduce the harmful effects on the gastrointestinal tract, extension, elimination of interaction of incompatible components in combination preparations, the protection of unstable substances is marked.Conclusion: the analysis showed the possibility of improving the antituberculosis drugs by creating more comfortable for the reception in the different conditions of dosage forms, as well as the use of antituberculosis drugs immobilization for reducing toxicity, increasing bioavailability and sustained action.